2013
DOI: 10.1017/s0263034613000153
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of laser induced micro-shock waves and hot core plasma in quiescent air

Abstract: We present our results on spatio-temporal evolution of laser plasma produced shockwaves (SWs) and hot core plasma (HCP) created by focused second harmonic (532 nm, 7 ns) of Nd-YAG laser in quiescent atmospheric air at f/#10 focusing geometry. Time resolved shadowgraphs imaged with the help of an ICCD camera with 1.5 ns temporal resolution revealed the presence of two co-existing sources simultaneously generating SWs. Each of the two sources independently led to a spherical SW following Sedov-Taylor theory alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
(50 reference statements)
1
25
0
Order By: Relevance
“…Optical diagnostics, including the schlieren technique, shadow technique and spectral analysis were used to study the kernel structure and combustion of laser ignition; thereby, the detailed process of flame development could be obtained [17]. Leela et al [18] used an Intensified Charge Coupled Device (ICCD) camera to study the development of laser-induced plasma in air and observed the self-radiation of plasma. They believed that when the energy is high enough, the leading edge of the laser beam first reached the breakdown threshold and produced plasma and the beam interacted with the trailing edge of the plasma later, creating two kernels.…”
Section: Introductionmentioning
confidence: 99%
“…Optical diagnostics, including the schlieren technique, shadow technique and spectral analysis were used to study the kernel structure and combustion of laser ignition; thereby, the detailed process of flame development could be obtained [17]. Leela et al [18] used an Intensified Charge Coupled Device (ICCD) camera to study the development of laser-induced plasma in air and observed the self-radiation of plasma. They believed that when the energy is high enough, the leading edge of the laser beam first reached the breakdown threshold and produced plasma and the beam interacted with the trailing edge of the plasma later, creating two kernels.…”
Section: Introductionmentioning
confidence: 99%
“…Before applying the energy deposition model, a steady solution with a bow shock wave has been obtained. When investigating the shape of the energy deposition region in previous studies [31,32], it was considered to be slightly asymmetric. So, in the present study, the shape of the focus was assumed to be an ellipsoid.…”
Section: Numerical Techniquesmentioning
confidence: 99%
“…It has been shown that the energy absorption rate of air increases with pulse interval (and also with energy per pulse) when the pulse interval is short enough for the electron density not to fully decay. The energy absorbed by the medium (air) was shown to saturate at approximately 60-70% of the incident beam energy [15,26,27] with increasing laser power. At high-enough laser energy levels, the inverse Bremsstrahlung takes place even prior to the laser beam reaching the optical focal point.…”
Section: Introductionmentioning
confidence: 99%
“…At high-enough laser energy levels, the inverse Bremsstrahlung takes place even prior to the laser beam reaching the optical focal point. In this case, two overlapping plasma cores are formed, one at the optical focal point and another one slightly closer to the focusing optics [25,26]. The resulting pressure wave is still a single pressure pulse (or monopole) because the development time of the plasma is still shorter than the time period of the generated acoustic pressure wave.…”
Section: Introductionmentioning
confidence: 99%